Role play as an educational strategy to strengthen basic social skills in early childhood. - Solano Rojas, Yessenia Fiorely (2025)
This article is based on applied research aimed at determining the effectiveness of the role-play program “Together is Better” in developing basic social skills in four-year-old children at an educational institution in Chiclayo. A quantitative approach with a pre-experimental design (pre-test–intervention–post-test) was used. The sample, selected for convenience, consisted of 27 students. The dependent variable (basic social skills) was assessed using an observation guide based on the Social Interaction Skills Questionnaire (CHIS), validated by expert judgment (V de Aiken = 1.00) and with adequate reliability (α = 0.837). The initial results showed a predominance of the basic level; after the application of 12 role-play workshops (spontaneous, guided, with materials, in small groups, and with conflict resolution), 77.78% reached the intermediate level and 22.22% reached the advanced level. It is concluded that the role-play strategy, structured within constructivist and experiential frameworks, significantly improves positive social expression, interpersonal communication, and cooperation and assistance in early childhood education.